Upaya Meningkatkan Kemandirian Belajar Siswa Melalui Lesson Study Kelas V SD Negeri 0605 Simanuldang - Alwi Hamdani Hasibuan; Rahma Sari Harahap; Mancar; Nurhayati Siregar (Dirosah Islamiyah, 2026)
Based on the research results, it can be concluded that: (1) The learning independence of class V students of SD Negeri 0605 Simanuldang pre-cycle is still low, namely 6 students or 20.00% learning independence is "very good", 5 students or 16.67% learning independence is "good", 10 students or 33.33% learning independence is "sufficient", 5 students or 16.67% learning independence is "less", and 4 students learning independence is "very lacking". (2) The increase in student learning independence through lesson study class V SD Negeri 0605 Simanuldang cycle I has begun to increase, namely 10 students or 33.33% learning independence is "very good", 8 students or 26.67% learning independence is "good", 9 students or 30.00% learning independence is "sufficient", 3 students or 10.00% learning independence is "less", there are no more students learning independence is "very lacking". In cycle II, the learning independence of fifth grade students of SD Negeri 0605 Simanuldang has increased, namely 18 students or 60.00% learning independence "very good", 12 students or 40.00% learning independence "good", no students learning independence "sufficient", no students learning independence "less", no students motivation "very less". So it can be concluded that through lesson study can improve the learning independence of fifth grade students of SD Negeri 0605 Simanuldang